Investigating EFL Learners’ Ability in Generating, Organizing, and Elaborating Ideas in an Argumentative Essay - M.Fadhly Farhy Abbas; Herdi Herdi (J-SHMIC : Journal of English for Academic, 2018)
This study aims at investigating EFL learners’ ability in generating, organizing, and elaborating ideas of argumentative essay. Quantitative method with descriptive quantitative design was employed in this study. To collect the data, the writing test and unstructured interview were used in this research. This research was conducted on April 2018 at Universitas Lancang Kuning, Pekanbaru. There were 46 learners selected as participants in this research. The result of the writing test showed that the learners’ mean score was 64.6 and it was categorized into low level of ability. Moreover, based on the interview the learners said that they felt difficult in elaborating ideas as well as organize the ideas in a good order. It was beacuse the learners had low alertness and carefulness in writing, low motivation to write an essay, low confidence when writing, and seldom to practice writing at leisure time. Therefore, appropriate writing strategy supported by suitable learning media is needed to facilitate and improve the learners’ ability in writing the essay. In conclusion, the learners’ ability in generating, organizing, and elaborating ideas is in low level of ability.